2020
DOI: 10.1186/s13023-020-1304-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human gene therapy for RPE65-associated Leber’s congenital amaurosis on visual function: a systematic review and meta-analysis

Abstract: Background: RPE65-associated LCA (RPE65-LCA) is an inherited retinal degeneration caused by the mutations of RPE65 gene and gene therapy has been developed to be a promising treatment. This study aims to evaluate the association between changes in visual function and application of gene therapy in patients with RPE65-LCA. Methods: Several databases (PubMed, Cochrane Library, and Web of Science) were searched for results of studies describing efficacy of gene therapy in patients with RPE65-LCA. Six studies, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 31 publications
2
44
2
Order By: Relevance
“…This therapy has an acceptable safety profile. However, the recent meta-analysis summarizing the results of six clinical trials, including 164 eyes, showed that efficacy in improving best-corrected visual acuity appears to be limited to 2 years after treatment [ 42 ]. Moreover, some tendency for thinning of the RPE layer faster in the treated eye than in the non-treated one was observed even in the first year after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This therapy has an acceptable safety profile. However, the recent meta-analysis summarizing the results of six clinical trials, including 164 eyes, showed that efficacy in improving best-corrected visual acuity appears to be limited to 2 years after treatment [ 42 ]. Moreover, some tendency for thinning of the RPE layer faster in the treated eye than in the non-treated one was observed even in the first year after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a hope to prolong the efficacy of the therapy. It is suggested to administer combinatorial agents supplementing the gene therapy to slow retinal degeneration in the long term [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, AAV vectors are the predominant candidate therapeutic options for tackling ocular diseases with a gene therapy to treat Leber congenital amaurosis based on the delivery of RPE65 by an AAV serotype 2 (AAV-2) vector having already been approved by the Food and Drug Administration (United States) and the European Medicines Agency ( Russell et al, 2017 ). Long-term efficacy of AAV-based RPE65 gene therapies appeared to be limited to 2 years after treatment ( Wang et al, 2020 ), however, a recent follow-up report on therapeutic outcomes confirmed that 86% of patients receiving this approved RPE65 gene therapy (named voretigene neparvovec) maintained improved visual function 4 years after the treatment ( Drack et al, 2019 ). More results are warranted as the study includes a 15-year follow-up of patients (NCT00999609).…”
Section: Genetic Therapies For Treating Irds: From Gene Augmentation mentioning
confidence: 99%
“…Despite recent advancements in therapeutic approaches for inherited retinal diseases, there is still a lack of an effective treatment for the main types of IRDs. One of the most advanced therapeutic options is gene therapy, with a treatment currently available for an aggressive form of RP, Leber Congenital Amaurosis, caused by mutations in the RPE65 gene [ 5 , 6 ]. However, to develop treatments for IRDs caused by mutations in all IRDs related-genes, complementary therapeutic options to gene therapy would be much welcomed.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the retina, a growing list of differentially expressed miRNAs has been described to be involved in retinal diseases, in both humans and animal models [ 21 ]. This includes miR-146a and miR-195 in diabetic retinopathy [ 22 , 23 ]; miR-9, miR-34a, miR-125b, and miR-155 in macular degeneration [ 24 , 25 ]; and miR-125a and miR-17 in retinoblastoma [ 6 , 26 ]. In RP, a common pattern of aberrantly expressed miRNAs, miR-1, miR-133, and miR-142, was observed in four murine models of the disease, involving different genes (rho and rds) and inheritance patterns [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%